Membrane-active peptides as anti-infectious agents - Rivas, Luis; Luque-Ortega, Juan Román; Fernández-Reyes, Maria; Andreu, David (Journal of Applied Biomedicine, 2010)
The lipid components of pathogen cell membranes have been considered as a poor pharmacological target, due to their universal distribution and apparent homogeneity throughout living organisms. Among the rare exceptions to this view one could mention polyene antibiotics such as amphotericin, or peptide antibiotics such as the polymyxins and the gramicidins. In the last two decades, however, the above notion has been challenged by two main lines of discovery; first, natural antimicrobial peptides (AMPs) that kill pathogens by interaction with phospholipids and membrane permeabilization, and secondly, cell-penetrating peptides (CPPs), capable of introducing into cells a variety of cargoes in the absence of specific receptors, again by interaction at some point with membrane phospholipids. For both AMPs and CPPs, the pharmacological proof-of-concept has been successfully demonstrated, and promising applications as nanobiotechnological tools have been envisaged though not hitherto materialized in clinical settings. In this review we briefly examine the pros and cons of these two classes of therapeutic agents, as well as strategies aimed at rationalizing and expanding their potentiality.
Keywords: financování organizované; Communicable Diseases; Animals; Cell Membrane Permeability; lipopolysacharidy; permeabilita buněčné membrány; kationické antimikrobiální peptidy; lidé; Drug Resistance, Microbial; infekční nemoci; Lipopolysaccharides; rostliny; Financing, Organized; peptidy; mikrochemie; Plants; Antimicrobial Cationic Peptides; zvířata; Microchemistry; Peptides; antibiotická rezistence; Humans